2021
DOI: 10.17977/um064v1i112021p1479-1493
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation between EFL Students' Use of ICT Level and Their Autonomous Learning Level

Abstract: Information and Communication Technology is a basic need for life nowadays, including education. Many people believe that ICT can promote students’ autonomous learning. Thus, this study was conducted to find whether ICT usage and autonomous learning are correlated, and to compare the attitudes between Indonesian and Moroccan EFL students. This study used quantitative correlational design. The participants were 97 English Department students of Universitas Negeri Malang. The instrument was a questionnaire with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…For example, a quantitative study with a non-experimental and cross-sectional design conducted by Nina-Cuchillo et al (2021) revealed that students' ICT and learning autonomy correlate. Similarly, Evita et al (2021) in a quantitative correlational study involving 97 participants from an English department in Indonesia found that students' degree of learning autonomy correlates with their ICT competence. Reinders and White (2016) point out that over the past two decades, developments in pedagogy in both ICT and autonomous learning have facilitated an increasing "fusion" or "convergence" of the two in ELT research and practice.…”
mentioning
confidence: 89%
“…For example, a quantitative study with a non-experimental and cross-sectional design conducted by Nina-Cuchillo et al (2021) revealed that students' ICT and learning autonomy correlate. Similarly, Evita et al (2021) in a quantitative correlational study involving 97 participants from an English department in Indonesia found that students' degree of learning autonomy correlates with their ICT competence. Reinders and White (2016) point out that over the past two decades, developments in pedagogy in both ICT and autonomous learning have facilitated an increasing "fusion" or "convergence" of the two in ELT research and practice.…”
mentioning
confidence: 89%